The role of zakat institution in facing covid-19: a case study of the federal territory Islamic council (MAIWP) of Malaysia - Hambari, Nursalam; Arif, Arif Ali; Artalim Zaim, Muntaha (Center of Strategic Studies, 2020)
In the beginning of 2020, the Coronavirus (Covid 19) appeared, which attacks humans and quickly turns into a global pandemic. Covid-19 has resulted in multidimensional crises such as health, economic, social, and lifestyle crises. Many people in different countries face difficulties in life. Therefore, Zakat as an Islamic social fund has a role in overcoming this crisis, by providing assistance to the communities which is directly affected by the crisis. This study aims to examine the role of Zakat in this crisis from the perspective of Islamic jurisprudence and its application in the zakat institution by taking the case of the Federal Territory Islamic Council (MAIWP) that has done various programmers in helping people who are directly affected by the crisis. This study uses two methods including inductive and analytical approaches to achieve its objectives. Among the most important results of the study: Zakat distribution programs conducted by Baitulmal-MAIWP for zakat beneficiaries affected by Covid-19, was to help ease the burden on ordinary people following the implementation of Movement Control Order (MCO) by the government due to the spread of the Covid-19 pandemic. This program is named “Bantuan Zakat Kecemasan Covid-19” (Zakat Emergency Aid Covid-19) or #MusaadahCovid19MAIWP.